America's Energy Future: Technology and Transformation - National Academy of Sciences; National Academy of Engineering; National Research Council (The National Academies Press, 2009)
For multi-user PDF licensing, please contact customer service. Energy touches our lives in countless ways and its costs are felt when we fill up at the gas pump, pay our home heating bills, and keep businesses both large and small running. There are long-term costs as well: to the environment, as natural resources are depleted and pollution contributes to global climate change, and to national security and independence, as many of the world's current energy sources are increasingly concentrated in geopolitically unstable regions. The country's challenge is to develop an energy portfolio that addresses these concerns while still providing sufficient, affordable energy reserves for the nation. The United States has enormous resources to put behind solutions to this energy challenge; the dilemma is to identify which solutions are the right ones. Before deciding which energy technologies to develop, and on what timeline, we need to understand them better. America's Energy Future analyzes the potential of a wide range of technologies for generation, distribution, and conservation of energy. This book considers technologies to increase energy efficiency, coal-fired power generation, nuclear power, renewable energy, oil and natural gas, and alternative transportation fuels. It offers a detailed assessment of the associated impacts and projected costs of implementing each technology and categorizes them into three time frames for implementation.
Keywords: Energy and Energy Conservation; Environment and Environmental Studies

Transitions to Alternative Vehicles and Fuels - National Research Council (The National Academies Press, 2013)
For a century, almost all light-duty vehicles (LDVs) have been powered by internal combustion engines operating on petroleum fuels. Energy security concerns about petroleum imports and the effect of greenhouse gas (GHG) emissions on global climate are driving interest in alternatives. Transitions to Alternative Vehicles and Fuels assesses the potential for reducing petroleum consumption and GHG emissions by 80 percent across the U.S. LDV fleet by 2050, relative to 2005. This report examines the current capability and estimated future performance and costs for each vehicle type and non-petroleum-based fuel technology as options that could significantly contribute to these goals. By analyzing scenarios that combine various fuel and vehicle pathways, the report also identifies barriers to implementation of these technologies and suggests policies to achieve the desired reductions. Several scenarios are promising, but strong, and effective policies such as research and development, subsidies, energy taxes, or regulations will be necessary to overcome barriers, such as cost and consumer choice.
Keywords: Energy and Energy Conservation; Earth Sciences

The Hydrogen Economy: Opportunities, Costs, Barriers, and R&D Needs - National Research Council; National Academy of Engineering (The National Academies Press, 2004)
The announcement of a hydrogen fuel initiative in the President’s 2003 State of the Union speech substantially increased interest in the potential for hydrogen to play a major role in the nation’s long-term energy future. Prior to that event, DOE asked the National Research Council to examine key technical issues about the hydrogen economy to assist in the development of its hydrogen R&D program. Included in the assessment were the current state of technology; future cost estimates; CO2 emissions; distribution, storage, and end use considerations; and the DOE RD&D program. The report provides an assessment of hydrogen as a fuel in the nation’s future energy economy and describes a number of important challenges that must be overcome if it is to make a major energy contribution. Topics covered include the hydrogen end-use technologies, transportation, hydrogen production technologies, and transition issues for hydrogen in vehicles.
Keywords: Energy and Energy Conservation

Coal: Research and Development to Support National Energy Policy - National Research Council (The National Academies Press, 2007)
Coal will continue to provide a major portion of energy requirements in the United States for at least the next several decades. It is imperative that accurate information describing the amount, location, and quality of the coal resources and reserves be available to fulfill energy needs. It is also important that the United States extract its coal resources efficiently, safely, and in an environmentally responsible manner. A renewed focus on federal support for coal-related research, coordinated across agencies and with the active participation of the states and industrial sector, is a critical element for each of these requirements. Coal focuses on the research and development needs and priorities in the areas of coal resource and reserve assessments, coal mining and processing, transportation of coal and coal products, and coal utilization.
Keywords: Energy and Energy Conservation; Industry and Labor

Electricity from Renewable Resources: Status, Prospects, and Impediments - National Academy of Sciences; National Academy of Engineering; National Research Council (The National Academies Press, 2010)
A component in the America's Energy Future study, Electricity from Renewable Resources examines the technical potential for electric power generation with alternative sources such as wind, solar-photovoltaic, geothermal, solar-thermal, hydroelectric, and other renewable sources. The book focuses on those renewable sources that show the most promise for initial commercial deployment within 10 years and will lead to a substantial impact on the U.S. energy system. A quantitative characterization of technologies, this book lays out expectations of costs, performance, and impacts, as well as barriers and research and development needs. In addition to a principal focus on renewable energy technologies for power generation, the book addresses the challenges of incorporating such technologies into the power grid, as well as potential improvements in the national electricity grid that could enable better and more extensive utilization of wind, solar-thermal, solar photovoltaics, and other renewable technologies.
Keywords: Energy and Energy Conservation

Real Prospects for Energy Efficiency in the United States - National Academy of Sciences; National Academy of Engineering; National Research Council (The National Academies Press, 2010)
America's economy and lifestyles have been shaped by the low prices and availability of energy. In the last decade, however, the prices of oil, natural gas, and coal have increased dramatically, leaving consumers and the industrial and service sectors looking for ways to reduce energy use. To achieve greater energy efficiency, we need technology, more informed consumers and producers, and investments in more energy-efficient industrial processes, businesses, residences, and transportation. As part of the America's Energy Future project, Real Prospects for Energy Efficiency in the United States examines the potential for reducing energy demand through improving efficiency by using existing technologies, technologies developed but not yet utilized widely, and prospective technologies. The book evaluates technologies based on their estimated times to initial commercial deployment, and provides an analysis of costs, barriers, and research needs. This quantitative characterization of technologies will guide policy makers toward planning the future of energy use in America. This book will also have much to offer to industry leaders, investors, environmentalists, and others looking for a practical diagnosis of energy efficiency possibilities.
Keywords: Energy and Energy Conservation

The Power of Change: Innovation for Development and Deployment of Increasingly Clean Electric Power Technologies - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Electricity, supplied reliably and affordably, is foundational to the U.S. economy and is utterly indispensable to modern society. However, emissions resulting from many forms of electricity generation create environmental risks that could have significant negative economic, security, and human health consequences. Large-scale installation of cleaner power generation has been generally hampered because greener technologies are more expensive than the technologies that currently produce most of our power. Rather than trade affordability and reliability for low emissions, is there a way to balance all three? The Power of Change: Innovation for Development and Deployment of Increasingly Clean Energy Technologies considers how to speed up innovations that would dramatically improve the performance and lower the cost of currently available technologies while also developing new advanced cleaner energy technologies. According to this report, there is an opportunity for the United States to continue to lead in the pursuit of increasingly clean, more efficient electricity through innovation in advanced technologies. The Power of Change: Innovation for Development and Deployment of Increasingly Clean Energy Technologies makes the case that America's advantages—world-class universities and national laboratories, a vibrant private sector, and innovative states, cities, and regions that are free to experiment with a variety of public policy approaches—position the United States to create and lead a new clean energy revolution. This study focuses on five paths to accelerate the market adoption of increasing clean energy and efficiency technologies: (1) expanding the portfolio of cleaner energy technology options; (2) leveraging the advantages of energy efficiency; (3) facilitating the development of increasing clean technologies, including renewables, nuclear, and cleaner fossil; (4) improving the existing technologies, systems, and infrastructure; and (5) leveling the playing field for cleaner energy technologies. The Power of Change: Innovation for Development and Deployment of Increasingly Clean Energy Technologies is a call for leadership to transform the United States energy sector in order to both mitigate the risks of greenhouse gas and other pollutants and to spur future economic growth. This study's focus on science, technology, and economic policy makes it a valuable resource to guide support that produces innovation to meet energy challenges now and for the future.
Keywords: Energy and Energy Conservation; Environment and Environmental Studies

Review of the Research Program of the FreedomCAR and Fuel Partnership: Third Report - National Research Council (The National Academies Press, 2010)
The public-private partnership to develop vehicles that require less petroleum-based fuel and emit fewer greenhouse gases should continue to include fuel cells and other hydrogen technologies in its research and development portfolio. The third volume in the FreedomCAR series states that, although the partnership's recent shift of focus toward technologies that could be ready for use in the nearer term--such as advanced combustion engines and plug-in electric vehicles--is warranted, R&D on hydrogen and fuel cells is also needed given the high costs and challenges that many of the technologies must overcome before widespread use. The FreedomCAR (Cooperative Automotive Research) and Fuel Partnership is a research collaboration among the U.S. Department of Energy, the United States Council for Automotive Research - whose members are the Detroit automakers--five major energy companies, and two electric utility companies. The partnership seeks to advance the technologies essential for components and infrastructure for a full range of affordable, clean, energy efficient cars and light trucks. Until recently, the program primarily focused on developing technologies that would allow U.S. automakers to make production and marketing decisions by 2015 on hydrogen fuel cell-powered vehicles. These vehicles have the potential to be much more energy-efficient than conventional gasoline-powered vehicles, produce no harmful tailpipe emissions, and significantly reduce petroleum use. In 2009, the partnership changed direction and stepped up efforts to advance, in the shorter term, technologies for reducing petroleum use in combustion engines, including those using biofuels, as well as batteries that could be used in plug-in hybrid-electric or all electric vehicles.
Keywords: Transportation and Infrastructure; Energy and Energy Conservation

Transitions to Alternative Transportation Technologies: A Focus on Hydrogen - National Research Council (The National Academies Press, 2008)
Hydrogen fuel cell vehicles (HFCVs) could alleviate the nation's dependence on oil and reduce U.S. emissions of carbon dioxide, the major greenhouse gas. Industry-and government-sponsored research programs have made very impressive technical progress over the past several years, and several companies are currently introducing pre-commercial vehicles and hydrogen fueling stations in limited markets. However, to achieve wide hydrogen vehicle penetration, further technological advances are required for commercial viability, and vehicle manufacturer and hydrogen supplier activities must be coordinated. In particular, costs must be reduced, new automotive manufacturing technologies commercialized, and adequate supplies of hydrogen produced and made available to motorists. These efforts will require considerable resources, especially federal and private sector funding. This book estimates the resources that will be needed to bring HFCVs to the point of competitive self-sustainability in the marketplace. It also estimates the impact on oil consumption and carbon dioxide emissions as HFCVs become a large fraction of the light-duty vehicle fleet.
Keywords: Energy and Energy Conservation; Environment and Environmental Studies

Coal: Energy for the Future - National Research Council (The National Academies Press, 1995)
The U.S. Department of Energy (DOE) was given a mandate in the 1992 Energy Policy Act (EPACT) to pursue strategies in coal technology that promote a more competitive economy, a cleaner environment, and increased energy security. Coal evaluates DOE's performance and recommends priorities in updating its coal program and responding to EPACT. This volume provides a picture of likely future coal use and associated technology requirements through the year 2040. Based on near-, mid-, and long-term scenarios, the committee presents a framework for DOE to use in identifying R&D strategies and in making detailed assessments of specific programs. Coal offers an overview of coal-related programs and recent budget trends and explores principal issues in future U.S. and foreign coal use. The volume evaluates DOE Fossil Energy R&D programs in such key areas as electric power generation and conversion of coal to clean fuels. Coal will be important to energy policymakers, executives in the power industry and related trade associations, environmental organizations, and researchers.
Keywords: Energy and Energy Conservation

Accelerating Decarbonization of the U.S. Energy System - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The world is transforming its energy system from one dominated by fossil fuel combustion to one with net-zero emissions of carbon dioxide (CO2), the primary anthropogenic greenhouse gas. This energy transition is critical to mitigating climate change, protecting human health, and revitalizing the U.S. economy. To help policymakers, businesses, communities, and the public better understand what a net-zero transition would mean for the United States, the National Academies of Sciences, Engineering and Medicine convened a committee of experts to investigate how the U.S. could best decarbonize its transportation, electricity, buildings, and industrial sectors. This report, Accelerating Decarbonization of the United States Energy System, identifies key technological and socio-economic goals that must be achieved to put the United States on the path to reach net-zero carbon emissions by 2050. The report presents a policy blueprint outlining critical near-term actions for the first decade (2021-2030) of this 30-year effort, including ways to support communities that will be most impacted by the transition.
Keywords: Environment and Environmental Studies; Energy and Energy Conservation

Hidden Costs of Energy: Unpriced Consequences of Energy Production and Use - National Research Council (The National Academies Press, 2010)
Despite the many benefits of energy, most of which are reflected in energy market prices, the production, distribution, and use of energy causes negative effects. Many of these negative effects are not reflected in energy market prices. When market failures like this occur, there may be a case for government interventions in the form of regulations, taxes, fees, tradable permits, or other instruments that will motivate recognition of these external or hidden costs. The Hidden Costs of Energy defines and evaluates key external costs and benefits that are associated with the production, distribution, and use of energy, but are not reflected in market prices. The damage estimates presented are substantial and reflect damages from air pollution associated with electricity generation, motor vehicle transportation, and heat generation. The book also considers other effects not quantified in dollar amounts, such as damages from climate change, effects of some air pollutants such as mercury, and risks to national security. While not a comprehensive guide to policy, this analysis indicates that major initiatives to further reduce other emissions, improve energy efficiency, or shift to a cleaner electricity generating mix could substantially reduce the damages of external effects. A first step in minimizing the adverse consequences of new energy technologies is to better understand these external effects and damages. The Hidden Costs of Energy will therefore be a vital informational tool for government policy makers, scientists, and economists in even the earliest stages of research and development on energy technologies.
Keywords: Energy and Energy Conservation